At the Origins of the Latvian Orthodox Church: from the “Russian Faith” to Autocephalous Tendencies - A. E. Kotov (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
The issue of the genesis of the national movement among the Latvian Orthodox population is considered. On the example of the fate of the leaders of the movement for Latvian church independence from Russian Orthodoxy - priest Janis Namnieks and prominent lawyer Janis Davis - the reasons for the appearance of this movement are established, the reasons for the failure of its supporters in 1920 are revealed. It was established that, contrary to popular belief, supporters of an early separation from the Russian Orthodox Church quickly moved from supporting the imperial authorities to the maximum displacement of the “Russian factor” from the life of the Orthodox in the new state - Latvia. It is emphasized that the lack of consolidated support of the secular authorities, the influence of the bishop who came from Russia, the ethnic Latvian John (Pommers), postponed this process for 15 years, and therefore, Latvian Orthodoxy did not go along the beaten path of their Estonian brothers. The attention to the emergence of a historiographic tradition of studying autocephalous tendencies among Latvian Orthodox parishes is paid. A comparison is made of the source base, which was used by researchers to build their own concepts. In addition to research papers and published sources, the article is based on materials from Latvian and Russian archives.